Optimization of medium composition for biomass production of recombinant Escherichia coli cells using response surface methodology - (:unkn) unknown (ELSEVIER, 2006)
Factorial designs and second order response surface methodology (RSM) for medium optimization were employed for the growth of recombinant Escherichia coli cells carrying a plasmid encoding TaqI endonuclease as a part of the fermentation strategy for general recombinant protein production. The method used was effective in screening for nutritional requirements using limited number of experiments. The concentrations of carbon source (glucose), inorganic nitrogen ((NH4)(2)HPO4), potassium (KH2PO4) and magnesium (MgSO4 center dot 7H(2)O) sources in medium were changed according to the central composite rotatable design consisting of 29 experiments, and the biomass yield was calculated. The optimum medium composition was found to be 15gL(-1) glucose, 6.6gL(-1) (NH4)(2)HPO4, 20.1 gL(-1) KH2PO4 and 1.7 gL(-1) MgSO4 center dot 7H(2)O. The model prediction of 2.72 gDCW L-1 biomass at optimum conditions was verified experimentally as 2.68 gDCW L-1 which is much higher than any value obtained in initial experiments as well as in studies carried out previously. The correlation between biomass growth and TaqI endonuclease enzyme yield obtained under the same medium compositions was also analyzed. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: medium design; recombinant DNA; enzyme production; response surface methodology optimization; TAQI RESTRICTION-ENDONUCLEASE; EXPRESSION